Angelika Frankenstein makes her match : a novel - Thorne, Sally, 1981- (Avon, an imprint of HarperCollinsPublishers, 2022)
"For generations, every Frankenstein has found their true love and equal, unlocking lifetimes of blissful wedded adventure. Clever, pretty (and odd) Angelika Frankenstein has run out of suitors and fears she may become the exception to this family rule. When assisting in her brother Victor's ground-breaking experiment to bring a reassembled man back to life, she realizes that having an agreeable gentleman convalescing in the guest suite might be a chance to let a man get to know the real her. For the first time, Angelika embarks upon a project that is all her own. When her handsome scientific miracle sits up on the lab table, her hopes for an instant romantic connection are thrown into disarray. Her resurrected beau (named Will for the moment) has total amnesia and is solely focused on uncovering his true identity. Trying to ignore their heart-pounding chemistry, Angelika reluctantly joins the investigation into his past, hoping it will bring them closer. But when a second suitor emerges to aid their quest, Angelika wonders if she was too hasty inventing a solution. Perhaps fate is not something that can be influenced in a laboratory? Or is Will (or whatever his name is!) her dream man, tailored for her in every way? And can he survive what was done to him in the name of science, and love? Filled with carriages, candlesticks, and corpses, Angelika Frankenstein Makes Her Match is the spooky-season romcom that reminds us to never judge a man by his cadaver!"--FantasticFiction.com.